Evaluasi Implementasi Balanced Scorecard Pada Departemen Manajemen IPB Sebagai Program Studi Berbasis Kinerja - Zainati Fakhrina; Jono M Munandar; Sukiswo Dirdjosuparto (Jurnal Manajemen dan Organisasi, 2017)
Department of Management in Bogor Agricultural University (IPB), is one of the academic units in IPB that supports the achievement of IPB’s objective to become a world class university. To support such objective, evaluation is conducted by monitoring activity and performance measurement using Balance Scorecard (BSC) approach. The purpose of this study was to determine priority of perspectives and strategy objectives by using Analytical Network Process (ANP) method, measure quality assessment performance in Department of Management year 2015, establish strategic inisiatives, and to figure Departement of Managements’ strategy map using Interpretive Structural Modeling (ISM) Method. The result of this study indicated that the main priorities of the four perspectives had been defined: Research and Academic Excellence perspective, Stakeholders perspective, Internal Business Processes perspective and Capacity Building perspective. Performance measurement resulted that 10 from 24 performance indicators didn’t achieve the target, and set 10 strategic initiatives to support strategy objective target achievement. Strategy mapping using ISM indicated that strategy objective “Lecturers’ and academic staffs’ competency strengthening” was the key element to support other strategy objectives achievement.